B-site disorder driven multiple-magnetic phases: Griffiths phase, re-entrant cluster glass, and exchange bias in Pr2CoFeO6 - Pal A.; Singh P.; Gangwar V.K.; Ghosh S.; Prakash P.; Saha S.K.; Das A.; Kumar M.; Ghosh A.K.; Chatterjee S. (My University, 2025)
The magnetic spin ordering and the magnetization dynamics of a double perovskite Pr2CoFeO6 have been investigated by employing the (dc and ac) magnetization and neutron powder diffraction techniques. The study revealed that Pr2CoFeO6 adopted a B-site disordered orthorhombic structure (Pnma). Furthermore, ab initio band structure calculations suggested an insulating antiferromagnetic ground state. Magnetization measurements revealed that the system possesses a spectrum of competing magnetic phases, viz., long range canted antiferromagnetic (AFM) spin ordering (TN ∼269 K), Griffiths-like phase, re-entrant cluster glass (TG ∼34 K), and exchange bias effects. The neutron diffraction study divulged the exhibition of a long range G-type of canted AFM spin ordering. The random nonmagnetic dilution of magnetic Fe3+ (high spin) ions by Co3+ (low spin) ions due to B-site disorder essentially played a crucial role in manifesting such magnetic properties of the system. © 2019 Author(s).